Analisis Perbedaan Kadar Hematokrit dalam Sampel yang Dihomogenisasi Sekunder Sebanyak 8 Kali yang Tidak Dihomogenisasi Sekunder - Mustika Hutabarat (Universitas Hang Tuah, 2023)
Background: Hematology examination is one of the activities in the clinical laboratory. Hematological examination is hematocrit examination. At hematocrit inspection one of the important things in the pre-analytical stage is the homogenization of samples. The delay in the examination that occurs causes the blood to settle therefore it is necessary to do secondary homogenization before the blood is examined using the tool. This study aims to see a difference in the results of hematocrit levels in samples that are not homogenized secondary and homogenized secondary 8 times. Method: This type of research is a pre-experiment using Static Group Comparation. The subject of this study was students of the Faculty of Health Sciences of Musi Charitas Catholic University who were selected in acidental sampling. The hematocrit level check in the sample uses the Sysmex XP-100 tool by using the Apature Impedance Counters method. . Samples were treated without secondary homogenization and homogenized 8 times. The sample measurement data was then tested using the Wilcoxon Sign Rank test with a 95% confidence level.Result: The sample examined as many as 30 samples had an average hematocrit level test result in samples given unhomogenized treatment was 65% and the average result of secondary homogenized sample examination was 8 times 39.9%. The results were statistically tested and showed a meaningful difference of p=0.000<0.05.Conclusion: There were differences in the results of hematocrit levels of samples that were not homogenized secondary and homogenized secondary 8 times.